Investigating telomere dynamics using standard and AuNP-based assays and developing an LRP-based nanoparticle drug - Bernert, Martin (University of the Witwatersrand, Johannesburg, 2023)
Telomere dynamics, specifically telomerase activity have been implicated in age-related diseases, such as CVD, Alzheimer’s disease, and cancer. This makes the accurate detection of telomerase activity within cell cultures and tissue samples a necessity. Conventional techniques have many drawbacks, including their very high cost. Therefore, this research aimed to develop a gold nanoparticle (AuNP)-based assay to determine telomerase activity. In the assay the extracted telomerase leads to a colour change in the solution through the addition of telomeric repeats and subsequent elongation of the synthetic telomeres attached to the AuNPs. This colour change is detectable using spectrophotometric readings and represents telomerase activity. This assay would be useful as an alternative to expensive existing telomerase activity kits as large batches of AuNPs can be synthesised inexpensively. Telomerase activity was successfully detected in both HEK-293 and WHCO-5 cells using this novel technique, although the sensitivity of the AuNP-based telomerase activity assay is currently lower than a commercially available qPCR-based telomerases activity kit. In addition, telomerase activity is directly affected by the LRP protein, a highly conserved non-integrin transmembrane receptor, which has been shown to have therapeutic effects in ageing, Alzheimer’s disease, Parkinson’s disease, diabetes, and cardiovascular disease models. Recently it has been found that overexpression of LRP::FLAG, by plasmid transfection, leads to a significant increase in telomerase activity in cell culture models. This may indicate that upregulation of LRP can be used to treat various age-related diseases, however, transfection is not a viable treatment strategy and therefore, a protein-based drug was created. For a protein-based drug, a suitable delivery system needed to be developed and nano-capsules, such as those synthesised using Poly(lactic-co-glycolic acid) (PLGA), are able to contain the therapeutic protein. The molecules contained within the nanoparticles also gain the benefit of having increased stability compared to unprotected molecules and the capsules have the capacity for surface modifications for targeted therapy. These polymer- based nanoparticles are also biodegradable and biocompatible, making them a safe delivery agent. Thus, this research further aimed to develop a PLGA-based LRP drug delivery system for the 37 kDa Laminin receptor protein. Both synthesis of the nanoparticles and encapsulation of the LRP protein were successfully optimised and the completed drug was tested in a cell culture model, where treatment increased cell viability and telomerase activity in HEK-293 cells. Therefore, this LRP drug delivery system has great potential to assist in the translation of our in vitro studies into an in vivo context. Due to the wide range of applications elevating LRP levels has in the treatment of different disorders, this could represent a safer alternative to plasmid transfection treatment and could potentially be used for the treatment of age-related diseases, through its ability to increase telomerase activity
Thesis Submitted in fulfillment of the requirements for the degree Philosophiae Doctor in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2023
Keywords: Telomerase; LRP/LR; PLGA; AuNP; UCTD; SDG-3: Good health and well-being